Pengaruh Pengawasan dan Pelatihan Terhadap Kinerja Karyawan - Terdjo, Edy (Fakultas Ekonomi Dan Bisnis Universitas Tjut Nyak Dhien, 2025)
Employee performance is considered important for the organization because the success of an organization is influenced by the performance itself. Performance or work performance is the work achieved by an employee in carrying out tasks according to the responsibilities assigned to him. Many factors can affect employee performance including supervision and training. This study intends to determine the effect of Supervision and Training on Employee Performance either partially or simultaneously. This type of research is a quantitative descriptive method. Research objects in this study are employees, totaling 48 people. The sampling technique uses the saturated sampling technique, which means the population is the same as the sample. The data analysis technique used is multiple regression analysis. The results showed partially and simultaneously the Supervision and Training affected the Employee Performance. In companies, it is advisable to monitor employee attitudes in working and socializing, making strict rules for employees who are often late and employees who are always unable to complete work on time. In connection with job training, companies are advised to hold training that is really by the needs of the company considering the number of costs that must be incurred during the implementation of training, using trainers who are experts in their fields, materials that are suitable for needs, methods that are easy to understand so that the training is held run effectively and efficiently so that in the end have an impact on improving employee performance.